Allocation of internally generated corporate cash flow in Africa. Issue 4 (5th November 2018) - Agyei-Boapeah, Henry; Machokoto, Michael
Abstract : Purpose: The purpose of this paper is to examine how managers of African firms, operating in environments characterised by less developed capital markets and weak institutional structures, make use of their internally generated cash flows. Design/methodology/approach: The authors use a panel data methodology which regresses a particular use of cash flow (e.g. capital expenditure) on the internally generated operating cash flow of a firm and a set of control variables. The estimation of the regression model is done by ordinary least squares regressions. For robustness, the authors also estimate the models using system generalised method of moments to control for endogeneity and measurement error problems. Findings: The authors find that managers of African firms hold most of their internally generated cash flows, and when they decide to spend, they allocate a higher proportion towards dividend payments; followed by debt adjustments; then to investments; and lastly, to equity repurchases. Research limitations/implications: The findings are consistent with the existence of a significant financial constraint in African markets, and the use of dividends to signal credit quality in relatively underdeveloped capital markets. Originality/value: The authors provide a more extensive analysis of how a firm spends a unit of the incremental cash flow it generates. In particular, the analysis shows that beyond investments in capital expenditure, other cash flow uses (i.e. cash holdings, dividend payments, and adjustments in debt and equity capital) which have been largely overlooked in the literature are important to understanding the effects of financial constraints on corporate decisions. Also, the early empirical evidence on the cash flow allocations of African firms could be a step in the right direction in informing theory development in this area.